Study on factors influencing caesarean section delivery in urban field practice area of Kamineni Institute of Medical Sciences, Narketpally, Nalgonda, India - Sarala Kumari, Balmur; Visweswara Rao, Guthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean section is one of the most commonly performed major surgeries in obstetric practice intended to save the mother and child in turn reducing maternal and perinatal mortality. The steadily increasing global rate of caesarean section has become one of the most debated topics in maternity care. The objective of this study is to identify the factors influencing caesarean section delivery in the study area. Methods: This is a community based cross sectional study conducted among 66 women who underwent caesarean section in urban slum of field practice area of KIMS Nalgonda from January 2017 to February 2017. Information regarding socio demographic factors, indication of caesarean section, maternal and neonatal outcome was recorded in pre-designed pretested questionnaire. Results: The rate of caesarean section (CS) in this study was 55.9%. The commonest indication for elective caesarean was previous caesarean section (59.5%) and for emergence caesarean section the commonest indication was fetal distress (50%). 47.6% in elective group and 62.5% in emergency underwent caesarean section in government hospitals, 52.38% in elective group and 37.5% in emergency underwent caesarean section in private nursing homes. Conclusions: Elective caesarean sections are more common than emergency sections. Most of the caesarian sections were in the age group of 18-25 years, Hindus, BC community, house wives, who have studied up to intermediate and above, below poverty line group and in multigravida women. Common indication for elective CS was previous CS and for emergency CS was fetal distress.